My beautiful journey : Kashmir to Kanyakumari - Gariyali, C. K. (Chennai, 2016)
This book is about Kashmir to Kanyakumari is an evocative story of a wide-eyed, small town girl.
Keywords: IAS as an author (Batch 1972)